Stimulus Duration in a Mixed Nerve Conduction Study: Decomposing Sensory Potential - ULUÇ, KAYIHAN (TURKISH NEUROLOGICAL SOC, 2020)
Objective: To decompose a part of the nerve action potential (NAP), mainly originating from large-myelinated sensory fibers, from mixed NAPs by using a stimulus with long duration during surface recordings. Materials and Methods: Median and ulnar mixed NAPs were elicited using submaximal stimulus intensities with 0.5 and 1.0-ms stimulus duration, which were adjusted to just below the threshold to activate motor fibers as detected visually through muscle twitch in hand muscles, by stimulating the median and ulnar nerves at the wrist and elbow and recording from the median and ulnar nerves at both the elbow and axilla, respectively. Healthy controls and patients with demyelinating neuropathy and/or motor conduction block were included in the study. Results: Mixed NAPs were recorded in 24 healthy subjects and three patients who had multifocal motor neuropathy (MMN), acute motor axonal neuropathy (AMAN), and ulnar entrapment neuropathy (UEN). Reference values were calculated in the healthy subjects. In patients with AMAN and MMN, mixed NAPs were normal, whereas in UEN, ulnar mixed NAPs had prolonged latencies. Conclusion: Mixed NAPs elicited by stimuli with long duration and low strength in the upper limbs can be used to detect sensory involvement at segments where motor conduction block exists and might help to classify demyelinating neuropathies.
Keywords: Mixed nerve conduction studies; stimulus duration; surface recording; demyelinating neuropathy; motor conduction block; H-REFLEX